(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: This paper, as a kind of simplified follow-up to an earlier study on international law enforcement research cooperation published in the first issue of Belügyi Szemle in 2011, attempts to take stock of the most important institutions that can be identified today for the support of research on law enforcement, albeit only in an exemplary manner. Methodology: Based partly on personal experience, the study describes and illustrates the institutional options available for improving law enforcement. It recalls a working group meeting convened by INTERPOL in 2010 and the main findings of the study that was carried out on that occasion. Findings: In particular, INTERPOL can be a useful catalyst for the coordination of police research and the practical application of scientific results in the fields of criminal law enforcement, criminology and international cooperation in criminal matters. Other voluntary institutions (e.g. AEPC) could provide a regular forum for sharing the results of research in police academics across continental boundaries. Value: The value of the study is to draw attention to the institutions that can be major catalysts for the cultivation and development of police science.